A custom‐made percutaneous flow‐restrictor to manage a symptomatic congenital porto‐systemic shunt in an infant. Issue 1 (4th May 2018) - Roggen, Mieke; Cools, Bjorn; Maleux, Geert; Gewillig, Marc
Abstract: Portosystemic shunts allow splanchnic blood to bypass the liver unfiltered, and may cause serious pulmonary and cerebral dysfunction; closure is therefore recommended. In patients where the portal system is hypoplastic, closure by a staged approach with a flow reducer may be necessary. We report a new, reliable, short, and adjustable device that can be delivered through a small 8‐Fr sheath.